Modern air conditioning practice - Harris, Norman C. (New York : McGraw-Hill, 1984)
A comprehensive text on the design, operation, and theory of air conditioning systems, covering thermodynamics, heat transfer, load calculations, refrigerants, system components, duct design, and control strategies.
Includes bibliographical references and index.
Keywords: Air conditioning systems; Heating, ventilating, air conditioning; HVAC (Heating, Ventilation, and Air Conditioning).; Heat transfer; Handbooks, manuals